Poupées japonaises. Présenter le Japon aux enfants français au début des années 1960 - Emmanuel Lozerand (Amnis)
In January 1961 two books were published to introduce Japan to francophone children: J’irai à Nagasaki [I will go to Nagasaki], a novel by Paul-Jacques Bonzon, author of the series "The six companions", in the "Green Library" by Hachette; and Noriko la petite Japonaise [Noriko the Little Japanese Girl], a picture-book with text and photographs by Dominique Darbois, in the collection "The Children of the World" by Fernand Nathan.These two works appear at the crossroads of two phenomena characteristic of the post-war period: the renewal of Western perception of Japan, and new developments in youth literature.Both are centered on the figure of a little Japanese girl. While in Noriko, the main character is likened to a doll, the novel I will go to Nagasaki confronts an imaginary Japan to a real one, and partially questions the theme of the Japanese doll.The two works progress on a narrow ridge line as they attempt to present the Japanese civilization in its peculiarity while integrating it into a common humanity. They also encourage us to reflect on the respective roles of fiction and documentary, of the novel and the picture-book, in the representation of reality.